The role of the Coulomb interaction in the formation of superconducting and pseudogap states in cuprate metal-oxides: Pseudogap - Pashitskii, E.A.; Pentegov, V.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
It is shown that the key role in the mechanism of high-Tc superconductivity in the layeredcuprate metal-oxides with anisotropic quasi-two-dimensional electronic spectrum and d-wave symmetry of the superconducting order parameter is played by the retarded screened Coulomb interaction and many-body correlations. We argue that the pseudogap observed in these materials is the anisotropic dielectric gap, which appears due to the electron-hole pairing on the flat portions of the Fermi surface in the vicinity of the extended saddle points in the quasiparticle spectrum. This gap coexists with the superconducting gap and is partially suppressed by scattering of current carriers on the charged point defects. The suppression of dielectric gap is analogous to the suppression of superconducting gap by magnetic impurities in «gapless» superconductors. The complete destruction of the pseudogap by charged impurities is assumed to increase Tc significantly.